Inner Conflict of Dewa's Character in the Novel Invalidite by Faradita: A Study of Humanistic Psychology - Raja Gukguk, M Evelina; Dicky Rachmat Pauji; Kurnia Rachmawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The objective of this research is to elucidate three key aspects related to Dewa's character in the novel